A qualitative investigation on work in NGOs: The case of Songkhla province of Thailand - Wesarat, Phathara-on (Macrothink Institute, 2013)
The concept of work in Non-Governmental Organizations (NGOs) specifically in Songkhla province of Thailand is highlighted in this paper.The study assumed that the meaning of work in NGOs is different from other types of organizations such as business and governmental organizations.NGO operations are seen to be different in terms of their goals when compared to those organizations. Even though research on work had been widely conducted in the business as well as the governmental sectors worldwide, few studies on this issue had been done in the NGO or non-profit sector.The concept of work in NGOs needs to be explored further in order for interested parties to get a true understanding of the nature of work in NGO sector.The research questions posed in this paper relate to how and why the work in NGOs influences the NGO professionals. The objective of this paper is to present some findings based on an in-depth study on the meaning of work in NGOs.This study consists of two core aspects of work: subjective and objective aspects.The respondents in this paper were 16 professionals (i.e. university graduates) selected from five local NGOs in Songkhla province of Thailand.This study used a mixed method within qualitative approach comprising in-depth interviews, non-participant observation, and secondary documents.This study showed that the NGO professionals had given high values on the subjective aspects of work because they were seeking fulfillment from work, while the objective aspects of work were seen to be less important to them.